1994
DOI: 10.1007/bf01476416
|View full text |Cite
|
Sign up to set email alerts
|

Peri-operative changes of cellular and humoral components of immunity with brain tumour surgery

Abstract: Nosocomial infections, which are not uncommon in neurosurgical intensive care medicine, may possibly be favoured by an impairment of immunological competence of the patient. In a prospective observational trial, we investigated several parameters of cellular and humoral immunity in 32 patients before and after resection of an intracranial tumour. We quantified the effects of operative procedure, dexamethasone pretreatment, and tumour type. Dexamethasone alone causes an increase of neutrophilic granulocyte coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, lymphocyte activity was significantly lower after surgery compared with the preoperative period, despite a notably increased count 28. T-helper cell and eosinophil levels were found to be lower in patients with intracranial malignant tumors (World Health Organization grade II–IV glioma) than in those with benign lesions, while immunoglobulin (Ig) M and neutrophil levels were higher 29. Previous studies have also reported that postoperative serum IgA and IgG levels were significantly reduced in patients with intracranial malignant tumors 30.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, lymphocyte activity was significantly lower after surgery compared with the preoperative period, despite a notably increased count 28. T-helper cell and eosinophil levels were found to be lower in patients with intracranial malignant tumors (World Health Organization grade II–IV glioma) than in those with benign lesions, while immunoglobulin (Ig) M and neutrophil levels were higher 29. Previous studies have also reported that postoperative serum IgA and IgG levels were significantly reduced in patients with intracranial malignant tumors 30.…”
Section: Discussionmentioning
confidence: 97%
“…Gliomas are known to produce immunodepression by releasing anti-inflammatory cytokines like IL-10, and soluble factors which have been reported earlier. [ 10 ] There were decreased levels of eosinophilic granules and T-helper cells, but higher levels of IgM in the glioma patients, compared to other neoplasms, thus depressing the cellular immunity. In our study, fair variability of tumors [ Table 4 ] has eliminated this likely bias.…”
Section: Discussionmentioning
confidence: 99%